RANCANG BANGUN APLIKASI MANAJEMEN SURAT BERBASIS WEB PADA PD. PASAR SURYA - Setiawan, Rahmat Iwan; Wurijanto, Tutut; Maulana, Yoppy Mirza (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2014)
The company's market Area (PDPS) is a company engaged in community service in place of fulfillment order, the means, and the infrastructure of traditional market in the city of Surabaya and the duties and responsibilities of a sub section of the administrative regulations based on SOP/TTU/01. Based on the four functions of SOP/TTU/01, in it there are processes that are currently experiencing difficulty in running it. This is due to the absence of the system (applications) that can help the performance of administrative sub division officer. The difficulty lies in the process of storage (tape/record keeping and archiving), search, retraction, distribution and provision of the code number. As for the duties and responsibilities of a sub section of the administrative regulations based on SOP/TTU/01. Based on the four functions of SOP/TTU/01, in it there are processes that are currently experiencing difficulty in running it. This is due to the absence of the system (applications) that can help the performance of administrative sub division officer. The difficulty lies in the process of storage (tape/record keeping and archiving), search, retraction, distribution and provision of the code number.